Deskripsi Upacara Odalan di Pura Payogan Agung Kutai Kalimantan Timur - Putra, Agus Kastama; Surya, Satyawati (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
The Odalan ceremony can be found in Hindu places of worship or temples in Bali, Java and Kalimantan. However, each region has its characteristics or specificities that are not found in other regions. It is an attraction for researchers to find out, explore, and discover the Odalan ceremony's uniqueness outside Bali, namely onKalimnantan. This study aims to describe the procedure or sequence of Odalan ceremonial activities, the cultural elements found in the Odalan ceremony, and the meaning of the Odalan ceremony's implementation. This research is descriptive qualitative research. The approach used is the ethnographic approach. The research object is the Odalan ceremony held at Pura Payogan Agung Kutai, East Kalimantan. This study's results indicate that the Odalan ceremony, which took place at Payogan Agung Kutai Temple, lasted for 71 days from 3 November 2019 to 12 January 2020. The sequence of activities started from the committee's formation, installing the attributes, cleaning the place for the ceremony until the Odalan Ceremony by carrying out prayers, Nyineb, until the committee's dissolution. The community was very enthusiastic in celebrating this ceremony, as evidenced by various parties' participation, both from Hindus themselves and the community around the temple. The Odalan ceremony was attended by Hindus from East Kalimantan, Bali, Java and Lombok. The Odalan or Piodalan ceremony is the anniversary of the birth of a Hindu holy place. In this case, the birthday of Pura Payogan Agung Kutai, East Kalimantan. Elements of Bali, Java, and Kalimantan (especially Dayak) culture, color the Odalan Ceremony at Pura Payogan Agung Kutai. The Odalan ceremony in each area is carried out according to local culture. Balinese, Javanese and Dayak cultural elements are reflected when presenting arts, offerings, tetabuhan, and dance.